Environmental education of students through the school chemistry course based on the principle of local history - Blazhko, Oleh; Blazhko, Alina (Personality and environmental issues, 2023)
The purpose of the article is to reveal the method of using elements of environmental knowledge based on the principle of local history in teaching some topics of the school chemistry course.The article establishes that environmentalization of educational subjects can be carried out by: introduction of elements of ecological knowledge when teaching some topics of various educational subjects; use of tasks, questions, problems of ecological content; carrying out interdisciplinary environmental activities; introduction of electives and optional courses in specialized classes; teaching ecology as a separate academic discipline.Chemistry, as an educational discipline, makes it possible to use the means of its subject to carry out environmental education of students directly in the learning process, provided that environmental knowledge becomes a function of chemical education. Since the school chemistry course has its own research subject, content, goal, tasks and learning methods, it is subject to both general didactic and specific learning principles. The principle of regionality, or local lore, belongs to the specific principles of teaching chemistry. The principle of local history involves introducing into the educational material information about the locality in which schoolchildren live, about the natural conditions, economy, ecological state of the native region with cognitive, scientific, educational, educational and practical purposes. The use of local history material in chemistry lessons helps to reveal general laws and phenomena that are studied, improves the depth of understanding of the educational material, increases interest in it, enriches students with knowledge about their native region, promotes the development of creative thinking and leads to an understanding of the main problems of their area.Тhe use of ecological material in the school chemistry course based on the principle of local history makes it possible to carry out environmental education of schoolchildren, which contributes to the awareness of students of the need for a careful attitude and rational use of natural resources.